DISTRIBUSI SPASIAL DAN TEMPORAL IKAN SIDAT (Anguilla sp.) YANG BERMIGRASI KEHULU DI SUNGAI TINOMBO KABUPATEN PARIGI MOUTONG - Syahril, Mohamad (JSTT, 2016)
Eels (genus  of Anguilla)  has long been the object  of intensive  research.  The province of Central  Sulawesi  has an abundant  source of eel seeds (glass eel phase)  especially  from the species  of Anguilla  marmorata.  The highest  abundance  of eel seeds occurs  during the period of dark moon along the estuaries  flowing  to the Tomini  Bay. The objectives  of the research were to study the species  diversity  of eels (Anguilla  sp.), to study the species  composition  of the eels, and to study the size structures  of the eels (Anguilla  sp.) migrating  upstream  to the River Tonombo.  Identification   of the eel samples  was conducted  by using morphometric method  that was the ratio between  predorsallength    (PD) and anadorsallength    (PA), and total length (TL). During  sampling  periods  there were three species  of eels identified  migrated upstream  to River Tinombo,  and they were Anguilla  marmorata,  A. selebecensis,   and one unknown  species  labelled  as Anguilla  sp. The species  of A. marmorata  had the highest abundance  (86%). It was followed  by A. celebecensis   (10%) and Anguilla  sp. (4%). Results showed  that spatially  the eels found  in River Tinombo  decreased  in number  but increased  in their weight.  While temporally,  their abundance  were different  each month.  It seemed that eels migrated  upstream  in order to grow.